If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 24 * 0 + 45 Multiply 24 * 0 y = 0 + 45 Anything times zero is zero. y = 0 + 45 Combine like terms: 0 + 45 = 45 y = 45 Solving y = 45 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 45
| 2n(6)+6=2(4n)+8 | | 21=-4.9x+25x | | p=3*5+8 | | 10x-19=9x+5 | | 12x+12=2x+282 | | 10x-200=3x-11 | | 10x-2=3x-11 | | 6x+31=9x-5 | | 4(4x)+2(x)=70 | | R/8=72 | | 10-x=x+8 | | 9(x+1)-4x=5-(x-3) | | 10x+3=6x-4 | | 4X-5X+8X-7=6X+6X+12 | | f(x)=24ln(x)-0.8x | | 2xy^2+4=2(3-x^2y)dy | | 3x-1+3x=12 | | y=24x+45 | | 2x+1+x+10+x-3=56 | | -3+2x-=3-4x | | 8x-4/2=10 | | tanx=-1.732 | | 1/14÷13/14 | | 9/10÷7/10 | | 2-(7/2y)-(39/4y^2)=0 | | -1x^2+23=0 | | 2x^4p^2-yzq-3z^2=0 | | 4n+25+3n+29=180 | | 24+x+x=90 | | (x+3)(x)=75 | | 3x+32+1=180 | | 6x-19+1=180 |